2022
DOI: 10.1186/s12913-022-08145-5
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals’ perceptions of patient safety culture and teamwork in intrapartum care: a cross-sectional study

Abstract: Background In complex healthcare organizations, such as intrapartum care, both patient safety culture and teamwork are important aspects of patient safety. Patient safety culture is important for the values and norms shared by interprofessional teams in an organization, and such values are principles that guide team members’ behavior. The aim of this study was 1) to investigate differences in perceptions of patient safety culture and teamwork between professions (midwives, physicians, nursing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 43 publications
1
18
0
1
Order By: Relevance
“…Similar to studies conducted in other countries [ 38 , 120 , 152 ], the findings from the current review indicated nurses from Latin American countries perceived higher levels of quality improvement and teamwork contributed to patient safety culture despite poor staffing. The impact of teamwork on patient safety culture probably results from nurses being the core hospital staff with the most direct contact with patients since they are responsible for the continuity of care from diagnostic and therapeutic management to hospital discharge [ 153 ].…”
Section: Discussionsupporting
confidence: 83%
“…Similar to studies conducted in other countries [ 38 , 120 , 152 ], the findings from the current review indicated nurses from Latin American countries perceived higher levels of quality improvement and teamwork contributed to patient safety culture despite poor staffing. The impact of teamwork on patient safety culture probably results from nurses being the core hospital staff with the most direct contact with patients since they are responsible for the continuity of care from diagnostic and therapeutic management to hospital discharge [ 153 ].…”
Section: Discussionsupporting
confidence: 83%
“…The future perspective should be to adopt strategies that contribute to developing a safety culture that reduces the frequency and severity of errors in healthcare institutions (Skoogh et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding professionals' perceptions of patient safety culture is critical to disseminating knowledge and increasing awareness, resulting in actions and improvements in the care of women (Skoogh et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations